Adsorption and corrosion behaviour of Trichoderma harzianum for AZ31B magnesium alloy in artificial seawater. (April 2017) - Qu, Qing; Li, Shunling; Li, Lei; Zuo, Limei; Ran, Xin; Qu, Yao; Zhu, Baolin
Highlights: Effect of Trichoderma Harzianum on the corrosion of AZ31B magnesium alloy was studied. Trichoderma Harzianum easily adsorbed on magnesium alloy surface and formed localized biofilm. Adsorption of Trichoderma Harzianum clearly decreased the pH and E corr values. Trichoderma Harzianum decreased the resistance of the localized corrosion. Abstract: Effect of the fungus, Trichoderma harzianum ( T. harzianum ), on the corrosion of AZ31 B magnesium alloy in artificial seawater (AS) has been studied. Hyphae of T. harzianum overlapped with corrosion products on the surface of AZ31 B magnesium alloy were clearly observed. Results showed that the presence of T. harzianum decreased the pH and E corr vs. SCE. Electrochemical results showed that i corr increased while R t decreased in the presence of T. harzianum obviously compared to the sterile AS, suggesting acceleration of the corrosion by T. harzianum . Cyclic polarization and SEM indicated that T. harzianum decreased the resistance of the localized corrosion.